Rape and buckwheat honey allergy in relation to heat treatment - KRETAVIČIUS, Justinas; DUBAKIENĖ, Rūta; BALŽEKAS, Jonas; ŠAFERIS, Viktoras (Acta medica Lituanica, 2010)
Introduction. Rape and buckwheat are progressively cultured in Lithuania. Pollen of these plants can be present in honeybee products, whereas it is known that pollen can be a potential allergen. Purpose. To explore how often and intensively the pollen of rape, buckwheat and mugwort, as well as monofloral (buckwheat and rape) and polyfloral (spring) honey can cause allergy in humans, to reveal whether there is a difference between honey allergy before and after heat treatment and to investigate the purity of monofloral honey in Lithuania. Materials and methods. The influence of allergens was determined by a skin-prick test. The botanical origin of honey and pollen was determined by the melissopalynological method. Results. Botanical composition studies have shown that in Lithuania where melliferous plants are cultivated, honey made by honeybees is almost homogeneous. The skinprick test revealed no statistically significant difference between honey tested before and after heat-treatment, but proved that monofloral honey was less allergenic than polyfloral. Pollen caused allergy more often and more intensively than monofloral honey did. Keywords: pollen, honey, allergy, heat treatment, skin-prick test